Acupuncture for substance use disorders: A systematic review and meta-analysis. (1st June 2016) - Grant, Sean; Kandrack, Ryan; Motala, Aneesa; Shanman, Roberta; Booth, Marika; Miles, Jeremy; Sorbero, Melony; Hempel, Susanne
Highlights: Available evidence did not yield consistent effects for substance use outcomes. Effects for withdrawal and anxiety symptoms were limited by low quality evidence. Effects did not differ systematically by adjunctive status or type of comparator. Abstract: Background: This systematic review aims to estimate the effects of acupuncture for adults with substance use disorders (SUDs). Methods: We searched 7 electronic databases and bibliographies of previous studies to identify eligible randomized trials. Two independent reviewers screened citations, extracted data, and assessed risks of bias. We performed random effects meta-analyses. We assessed quality of evidence using the GRADE approach. Results: We included 41 studies with 5, 227 participants. No significant differences were observed between acupuncture and comparators (passive controls, sham acupuncture, treatment as usual, and active interventions) at post-intervention for relapse (SMD −0.12; 95%CI −0.46 to 0.22; 10 RCTs), frequency of substance use (SMD −0.27; −2.67 to 2.13; 2 RCTs), quantity of substance use (SMD 0.01; −0.40 to 0.43; 3 RCTs), and treatment dropout (OR 0.82; 0.63 to 1.09; 22 RCTs). We identified a significant difference in favor of acupuncture versus comparators for withdrawal/craving at post-intervention (SMD −0.57, −0.93 to −0.20; 20 RCTs), but we identified evidence of publication bias. We also identified a significant difference in favor of acupuncture versus comparators for anxiety at post-intervention (SMD −0.74, −1.15 to −0.33; 6 RCTs). Results for withdrawal/craving and anxiety symptoms were not significant at longer follow-up. Safety data (12 RCTs) suggests little risk of serious adverse events, though participants may experience slight bleeding or pain at needle insertion sites. Conclusions: Available evidence suggests no consistent differences between acupuncture and comparators for substance use. Results in favor of acupuncture for withdrawal/craving and anxiety symptoms are limited by low quality bodies of evidence.